Feasibility of bone marrow mesenchymal stem cells harvesting from forearm bone - Tulyapruek Tawonsawatruk; Thepparat Kanchanathepsak; Thitinat Duangchan; Kuneerat Aswamenakul; Aungkura Supokawej (Heliyon, 2021)
Introduction: Mesenchymal stem cell is a promising therapeutic option in orthopedic filed and regenerative medicine. The feasibility of isolation method and characterization of Mesenchymal stem cell including growth kinetics, immunophenotypes and differentiation potency from small volume aspiration harvested from ulna and radius should be evaluated in order to utilize this cell in hand surgery. Materials and methods: Mesenchymal stem cells were isolated and characterized from bone marrow of 12 patients who underwent internal fixation of fractures at radius or ulna. Population doubling time & clonogenic ability, immunophenotypes and trilineage differentiation potential of Mesenchymal stem cells were evaluated. Results: Mesenchymal stem cells derived from bone marrow were attached to plastic flasks and became homogenous monolayer of fibroblast-like cells. They exhibited clonogenic ability and demonstrated positive markers which were shown by CD 73, CD 90, and CD 105 and negative markers which were shown by CD 34, CD 45. Mesenchymal stem cells derived from this source were capable of osteogenesis, chondrogenesis and adipogenesis. Discussion: This study demonstrated the feasibility of bone marrow mesenchymal stem cells harvested from forearm bone marrow with small volume samples. This source should be useful in tissue engineering strategy or orthobiologic approach in orthopedic surgery.